The Influence of Transformational Leadership, Organizational Culture, and Organizational Commitment on Innovative Work Behavior in Employees of PT. Herba Emas Wahidatama, Purbalingga Regency - Gemasari, Agustin Putriyana; Endratno, Hermin; Widhiandono, Hengky; Rahmawati, Ika Yustina (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine the influence of Transformational Leadership, Organizational Culture, and Organizational Commitment on Innovative   Work   behavior   at   PT   Herba   Emas Wahidatama. The population in this study was 108 employees of   PT Herba       Emas Wahidatama employees, with a research sample of the entire   population.   This   type   of   research   is   a quantitative  method.  Questionnaires  were distributed in December-January. The primary data is used using the saturated sampling method. Instrument test: reliability test, classic assumption test:   normality   test,   multicollinearity   test,   and heteroscedasticity test. The next tests are the model suitability test, multiple regression analysis, partial t- test, and the determinant coefficient R2 using the SPSS data analysis tool 26. The results of the study that have been obtained show that transformational leadership affects innovative work behavior, organizational culture  does  not  affect  innovative work behavior, and organizational commitment has no effect on innovative work behavior.